TVET in The 21st Century: Exploring Multimedia Elements in Digital Teaching and Learning Based On Art Content - Razali , Siti Soleha; Ismail, Affero; Md Yazid, Fatimah; Fazrulhelmi Ahmad , Mohammad; Hashim, Suhaizal; Rohanai, Reyanhealme; Mohamed Shafieek , Muhammad Shahrir (Journal of Technical Education and Training, 2023)
Research in digital teaching and learning (T&L) focusing on multimedia elements based on art content is essential in enhancing the quality of the curriculum delivery. In addition, research on art content in digital T&L for Technical and Vocational Education and Training (TVET) is limited. Thus, this paper explores the elements of multimedia components in T&L for TVET based on art content. Art content refers to the subject matter or the message conveyed by the presentation. The research utilizes the Fuzzy Delphi Method (FDM) as methodology. In the first phase, five experts specializing in multimedia and art were interviewed. After finalizing the interview results, a matrix analysis that combines the literatures finding was developed in order to determine the multimedia elements based on the art content. In the second phase, nine experts, including five from the first phase, validated the elements using the instrument. By using the Fuzzy Delphi Method, average values of m1, m2, and m3, ’d’ or Threshold value, expert’s consensus and Fuzzy Evaluation were derived from the data. Findings indicates that forty items out of four components which are emotional, subjective, execution, and psychological have been validated by the experts and reach 75 per cent of consensus. In conclusion, multimedia components based on art content in digital T&L for TVET should be utilized as a reference in developing digital content to provide future T&L standards for educators.